LOSSES OF UKRAINE'S SOCIAL INFRASTRUCTURE DUE TO WAR - PASIEKA, Igor; KINASH, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Social infrastructure plays an important role for the successful functioning of the state and for every citizen. It is designed to provide favorable living conditions for the population, has a positive impact on the development of the social production sector, and serves as a factor in territorial development and reproduction of the population. The war has become a real challenge for Ukraine and has caused systemic changes in the social infrastructure, leading to serious negative consequences for society. The purpose of the article is to study the losses of social infrastructure during the war. The following components are distinguished: educational, healthcare, culture, sports, tourism, and housing infrastructure. It is established that the infrastructure of preschool, general secondary, and vocational education is one of the most affected by the war in terms of the number of destroyed, damaged, and lost facilities. The dynamics of its losses during the war is presented.The losses of healthcare infrastructure are significant. The losses of cultural infrastructure, which represents the cultural heritage of UNESCO, are studied. The losses of residential infrastructure are studied. It was found that apartment buildings in Donetsk, Luhansk, Kharkiv, and Kherson regions suffered the greatest destruction. In many settlements, more than 50% of the buildings were destroyed or damaged, and in such cities as Bakhmut, Avdiivka, and Lysychansk, more than 90% of the facilities were damaged.The most affected regions require urgent measures to restore infrastructure and housing. Effective coordination of the authorities, civil society organizations and international partners is essential to ensure the rapid and effective restoration of damaged facilities and support for affected citizens. The government is setting a goal to restore what is critical to people's lives. The emphasis is on priority areas. Among them is the rebuilding of social infrastructure. Such reconstruction involves improving the quality of these facilities based on the principle of “restoring better than before.”
Keywords: social infrastructure; war; society